Extraction Rate in Vapor Assisted Extraction of Heavy Oil (VAPEX) - Vijitha Mohan; Parthasakha Neogi (Improved Oil and Gas Recovery, 2019)
Heavy oil recovery requires either heat (SAGD) or a solvent (VAPEX) to reduce its high viscosity first and then the less viscous oil can be recovered. We show here that the existing data on oil recovered in VAPEX process in sandpacks show a square root dependence on the height of pay zone, following expectation. This dependence had remained uncertain and is of importance in oil field operation.